The Middle Jurassic (Bajocian–Bathonian) flora of the Tabas Block, central Iran - Maleki, Saeed (Geologos, 2024)
The present study discusses the outcome of palynlogical and palaeobotanocal investigations of Middle Jurassic strata of the Tabas Block. The most commonly identified spore type is a trilete spore, Klukisporites, which accounts for 30 per cent, and the genus Ischyosporites which makes up 12 per cent of the spore collection. Plant fossils recovered from the borehole studied are indicative of a varied assemblage, starting with a diverse range of ferns and followed by Cycadophytes, Ginkgophytes and Coniferophytes. The predominance of the Lowland group in the Tabas Block during the Bajocian–Bathonian, as indicated by the Sporomorph EcoGroup (SEG) and Plant EcoGroup (PEG) models, suggests that the strata studied were laid down mainly in a lowland environment. Dinoflagellate cysts were found in locations that correspond to river and coastal ecogroups, hinting at marine influence.